2007
DOI: 10.1097/brs.0b013e3180bc219e
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Management of Degenerative Lumbar Spondylolisthesis

Abstract: Spinal fusion may lead to a better clinical outcome than decompression alone. No conclusion about the clinical benefit of instrumenting a spinal fusion could be made. However, there is moderate evidence that the use of instrumentation improves the chance of achieving solid fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(144 citation statements)
references
References 19 publications
6
129
0
6
Order By: Relevance
“…None of the studies were able to find a significant difference, probably since the incidence of complications was too low to detect a statistically significant difference. Older studies that were not included in this review showed higher complication rates in the fusion group [9,31], with a more recent study by Deyo et al [17] clearly showing significant higher complications rates in the decompression and fusion group compared to the decompression alone group. After adjusting for age, comorbidities and other factors, there was a higher risk of life-threatening life-events for patients receiving decompression with concomitant fusion.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…None of the studies were able to find a significant difference, probably since the incidence of complications was too low to detect a statistically significant difference. Older studies that were not included in this review showed higher complication rates in the fusion group [9,31], with a more recent study by Deyo et al [17] clearly showing significant higher complications rates in the decompression and fusion group compared to the decompression alone group. After adjusting for age, comorbidities and other factors, there was a higher risk of life-threatening life-events for patients receiving decompression with concomitant fusion.…”
Section: Discussionmentioning
confidence: 64%
“…However, the optimal surgical treatment in patients suffering from symptomatic lumbar stenosis, who also have degenerative spondylolisthesis, has long been a subject of debate. Decompression without fusion for lumbar stenosis in the presence of degenerative spondylolisthesis has been associated with postoperative instability of the spine [5][6][7][8][9][10]. This postoperative instability is presumed to be the result of the removal of the posterior elements, such as the spinous process, inter-and supraspinous ligaments and medial aspect of the facet joints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This practice is not supported through scientific data, while evidence supporting fusion in degenerative spondylolisthesis (slip of two adjacent vertebra), intuitively associated with progressive postsurgical spinal ''instability'', is lacking as well [28,29]. Besides the paucity of data reporting a clear beneficial effect of instrumented fusion, these ''advanced'' techniques are associated with an almost threefold risk of life-threatening complications.…”
Section: Decompression Versus Decompression With Instrumented Fusionmentioning
confidence: 99%
“…Furthermore, there are different subtypes of LSS, but little is known about what characterizes these subtypes in terms of pain, function and HRQoL. The effect of a concomitant spinal fusion in LSS surgery is debated since data is conflicting (Herkowitz and Kurz 1991;Bridwell et al 1993;Mardjetko et al 1994;Grob et al 1995;Katz et al 1997;Ghogawala et al 2004;Matsudaira et al 2005;Martin et al 2007;Försth et al 2013).…”
Section: The Current Situationmentioning
confidence: 99%